2024
DOI: 10.1029/2023ef003846
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Urban Form on the Spatial Pattern of Precipitation

Yanle Lu,
Zhou Yu,
John D. Albertson
et al.

Abstract: Urban areas are known to modify the spatial pattern of precipitation climatology. Existing observational evidence suggests that precipitation can be enhanced downwind of a city. Among the proposed mechanisms, the thermodynamic and aerodynamic processes in the urban lower atmosphere interact with the meteorological conditions and can play a key role in determining the resulting precipitation patterns. In addition, these processes are influenced by urban form, such as the impervious surface extent. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A similar performance has also been observed recently in the United States. Lu et al (2024) revealed that city size is positively correlated with the downwind precipitation enhancement under dominant wind direction. In summary, anthropogenic-related driving factors significantly influence the intensified shorter-duration heavy precipitation in urban regions, especially in humid regions and larger UACs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar performance has also been observed recently in the United States. Lu et al (2024) revealed that city size is positively correlated with the downwind precipitation enhancement under dominant wind direction. In summary, anthropogenic-related driving factors significantly influence the intensified shorter-duration heavy precipitation in urban regions, especially in humid regions and larger UACs.…”
Section: Discussionmentioning
confidence: 99%
“…Yao & Huang, 2023;Zhu et al, 2019). Particularly, this phenomenon is pronounced in downwind areas of cities (Hand & Shepherd, 2009;Lorenz et al, 2019;Lu et al, 2024). Conversely, some studies argued that urbanization may inhibit the development of convection and in turn reduce precipitation (J.…”
Section: Introductionmentioning
confidence: 99%